SHIP CLEARANCE IN AND CLEARANCE OUT SERVICES AT PT. SAUH BAHTERA SAKTI JAKARTA - Indriana Kristiawati; Kamsariaty Kamsariaty; David Bastian Sihombing (Jurnal Scientia, 2023)
The purpose of this study was to determine the procedures for permits in and out of ships belonging to PT. Sauh Bahtera Sakti Jakarta. This study uses a qualitative descriptive approach. Data collection methods are divided into 4 parts, namely: direct observation in the field, interviews or interviews with branch heads and staff or employees of PT. Sauh Bahtera Sakti Jakarta, the documentary method is related to the documents required during the clearance in and out of the ship, the literature study method related to the procedures for clearance in and out of the ship. From the results of Key's research that in the activities of clearance in and clearance out of ships, the outside service PT. Sauh Bahtera Sakti Jakarta is required to carry out activities correctly and quickly. The procedure has been done well. All activities have been organized to reduce errors when carrying out clearance in and out of the ship.